Validación de un instrumento para evaluar competencias de desarrollo personal en estudiantes universitarios. - García Rivera, Maribel; Rodríguez Fernández, Rosendo (Universidad Antonio Nariño, 2021)
The results of the validation process of a proposal for the evaluation of personal development competencies for university students are presented. It is a Likert scale, consisting of 143 items, which includes the measurement of five competences: Self-awareness, Healthy lifestyles, axiological competence, knowledge of the environment and social skills. The instrument was initially submitted to experts; after the relevant changes were made, a pilot was carried out with 100 subjects for statistical validation. The results indicate the validity and reliability of the instrument with a Cronbach's Alpha of 0.97, to that extent it has high applicability in the context for which it was designed.